The Impacts of Management Capacity on the Implementation of Merdeka Belajar Kampus Merdeka Policy in Higher Education - Thahir, Muthahharah; Widiawati, Widiawati; Rapida, Ida (Universitas Jambi, Indonesia, 2023)
This research aimed to examine the impacts of management capacity on the implementation ofÂ Merdeka Belajar Kampus MerdekaÂ policy in higher education. This research used the quantitative method with a correlational descriptive technique. The respondents were the head of the departments and the secretary of the departments. The data collection technique used in this research was a Likert scale questionnaire consisting of 5 alternative answers. The data analysis technique used was a product-moment correlation and simple linear regression analyses by using Â the SPSS Version 24 program. The results showed that management capacity had a significant effect on MBKM implementation of 57.5%. The rest was affected by other variables. The implication of this research is the need to increase the capacity of higher education management so the Merdeka Belajar Kampus Merdeka policy can be implemented more optimally.